2021
DOI: 10.1039/d1cp00418b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, magnetic, vibrational, and X-ray spectroscopy of inverse full-Heusler Fe2IrSi alloy

Abstract: The electronic, magnetic, structural, vibrational, and X-ray absorption spectroscopy of inverse full-Heusler Fe2IrSi alloy has been studied from density functional theory (DFT). The XA-phase with FM-configuration is the most stable one, structurally and thermodynamically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…For the practical application of any materials, knowledge of the melting temperature is highly needed. In this regard, we have calculated the melting temperature ( T m ) of Na 2 GeO 2 under different applied pressures by employing the equation given as , T normalm = 553 + 5.911 C 11 ± 300 …”
Section: Resultsmentioning
confidence: 99%
“…For the practical application of any materials, knowledge of the melting temperature is highly needed. In this regard, we have calculated the melting temperature ( T m ) of Na 2 GeO 2 under different applied pressures by employing the equation given as , T normalm = 553 + 5.911 C 11 ± 300 …”
Section: Resultsmentioning
confidence: 99%
“…Beyond atomic and ionic radius simulation, temperature plays an important role in structural stability. We calculated the melting temperature (T m ) of the investigated compounds CsGeX 3 (X = Cl, Br, and I) in this regard by using the equation given as [53,76,77] T m = 553 + 5.911C 11 ± 300 (13) The calculated melting temperatures are shown in Table 7 and from the obtained results, we observed that the melting temperatures increase from CsGe (Cl →Br →I) 3 with the I-atom containing compound possessing a melting temperature of upto 709.877 ± 300 which reveals that among the three compounds, it can maintain its structural stability even at high temperatures as compared with the other two compounds.…”
Section: Melting Temperaturementioning
confidence: 99%
“…Herein, some important parameters such as machinable factor (μ m ), Frantsevich’s ratio ( G / B ) and melting temperature ( T m ) which are very much needed in practical applications for thermoelectric materials are also calculated by employing the equations given as .25ex2ex μ normalm = B C 44 T normalm = ( 553 + 5.91 C 11 ) ± 300 …”
Section: Resultsmentioning
confidence: 99%